Exact solution of the Biswas-Milovic equation by Adomian decomposition method - Ahmed, Iftikhar; Mu, Chunlai; Zhang, Fuchen (International Journal of Applied Mathematical Research, 2013)
This paper studies the exact solution of the Biswas-Milovic equation with Kerr law nonlinearity by the aid of Adomian decomposition method. Biswas-Milovic equation is a generalized version of the familiar nonlinear Schrodinger's equation describing the propagation of solitons through optical fibers for trans-continental and trans-oceanic distances.